Separation of cucurbitane triterpenoids from bitter melon drinks and determination of partition coefficients using vortex‐assisted dispersive liquid‐phase microextraction followed by UHPLC analysis. Issue 10 (27th April 2017) - Hu, Shuang; Wang, Yan‐Hong; Avula, Bharathi; Wang, Mei; Khan, Ikhlas A
Abstract : A rapid, effective method applying vortex‐assisted liquid–liquid microextraction before ultra‐high performance liquid chromatography with mass spectrometry and evaporative light scattering detection was developed for the analysis of four cucurbitane triterpenoids (momordicoside L, momordicoside K, momordicoside F2, and 3β, 7β, 25‐trihydroxy cucurbita‐5, 23( E )‐dien‐19‐al) in bitter melon juices. Variables affecting the extraction efficiency including different extraction solvents, volume of extraction solvent, salt amount, acid condition, vortex speed and time were optimized thoroughly. Under the optimum conditions, precision was determined by the intra‐ and inter‐day tests in a range of 1.1–5.7% and 2.9–4.0% (RSD), respectively, with recoveries between 95.7 and 106.1%. The calibration curves showed good linearity with square correlation coefficient of 0.9936–0.9991 (evaporative light scattering detection) and 0.9858–0.9989 (MS). The detection limits ranged from 0.8–1.9 ng/mL (MS) to 3–10 ng/mL (evaporative light scattering detection) for these compounds. Enrichment factors of four target compounds were between 27 and 63 times. The proposed method was also used to determine the apparent solvent/water partition coefficients of analytes within the range of 53–120. The developed method can effectively enrich and quantify cucurbitane triterpenoids from bitter melon drinks.